Intrinsically Disordered Proteins Studied by NMR Spectroscopy - Felli, Isabella C.; Pierattelli, Roberta (Advances in Experimental Medicine and Biology, 2015)
This book discusses the paradigm-shifting phenomenon of intrinsically disordered proteins (IDPs) and hybrid proteins containing ordered domains and functional IDP regions (IDPRs). The properties of IDPs and IDPRs are highly complementary to those deriving from the presence of a unique and well-defined three-dimensional fold. Ignored for a long time in high-resolution studies of proteins, intrinsic protein disorder is now recognized as one of the key features for a large variety of cellular functions, where structural flexibility presents a functional advantage in terms of binding plasticity and promiscuity and this volume explores this exciting new research. Recent progress in the field has radically changed our perspective to study IDPs through NMR: increasingly complex IDPs can now be characterized, a wide range of observables can be determined reporting on the structural and dynamic properties, computational methods to describe the structure and dynamics are in continuous development and IDPs can be studied in environments as complex as whole cells. This volume communicates the new exciting possibilities offered by NMR and presents open questions to foster further developments. Intrinsically Disordered Proteins Studied by NMR Spectroscopy provides a snapshot to researchers entering the field as well as providing a current overview for more experienced scientists in related areas.